A Nutrition Education Intervention Positively Affects the Diet–Health-Related Practices and Nutritional Status of Mothers and Children in a Pulse-Growing Community in Halaba, South Ethiopia - Getahun Ersino Lombamo; Carol J. Henry; Gordon A. Zello (Children)
Objective: We conducted a six-month nutrition education intervention focused on the consumption of pulses and other foods to assess the effect on knowledge, attitude and practice (KAP) as well as the nutritional status of children and mothers from two pulse-growing communities in Halaba, south Ethiopia. Methods: About 200 mother–child pairs in each of two purposively selected communities participated in this intervention study. A six-month nutrition education programme, involving interactive monthly community meetings and home visits, was offered to one of the two communities and the other served as a control/comparison. This study incorporated the use of Health Belief Model constructs to assess the KAP/perceptions of mothers surrounding pulse and other food consumptions, as well as nutrition-related issues before and after the intervention. Objective measures included dietary diversity scores (DDSs), one-day weighed dietary intakes and nutritional status measures based on anthropometric information. Demographics and socioeconomic information were also collected at baseline and endline. Results: Significant improvements (p < 0.05) were found in the intervention group on the KAP and perceptions of pulse nutrition benefits among mothers, DDSs and pulse and animal source food consumption indexes for mothers and children and the mean body-mass-index-for-age Z-score and wasting among children. Conclusions: Community-based nutrition education interventions involving monthly interactive community meetings and home visits in pulse-growing communities from a resource-poor country like Ethiopia can be effective in improving mothers’ knowledge of pulse nutrition and consumption frequency, leading to improvements in the DDSs of children and mothers while decreasing child underweight and wasting.